1978
DOI: 10.1111/j.1471-0528.1978.tb10458.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maternal Glucose Ingestion on Fetal Breathing and Body Movements in Late Pregnancy

Abstract: Summary Fetal breathing movements and fetal whole body movements were observed over 2 hours in 22 normal singleton pregnancies between 34 and 38 weeks gestation using a real time ultrasonic B scan method. The proportion of time fetuses spent making breathing movements increased from 9.9 per cent to 48.3 per cent within one hour of their fasting mothers taking a 50 g glucose drink. Fetal whole body movements were not increased after maternal glucose ingestion. Arousal of the fetal central nervous system seems d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 10 publications
2
13
0
1
Order By: Relevance
“…There is some evidence that maternal hyperglycemia does affect fetal movement during the 3rd trimester in normal pregnancies (Aladjem, Feria, Rest, Gull, & O'Connor, 1979;Edelberg, Dierker, Kalhan, & Rosen, 1985;Gelman, Spellacy, Wood, Birk, & Buhi, 1980;Goodman, 1980). However, none of the studies has focused on cyclic motility, the direction of the effects are not consistent between studies, and numerous others have reported no effects (e.g., Bocking, Adamson, Cousin, Campbell, Carrnichael, Natale, & Patrick, 1982;Lewis, Trudinger, & Mangez, 1978;Natale, Richardson, & Patrick, 1983) including two studies of diabetics (Holden, Jovanovic, Dmzin, & Peterson, 1984;Wladimiroff & Roodenburg, 1982). Finally, the evidence from the present study linking parametric changes in cyclic motility with maternal glucose control must be tempered by the fact that the transient absence of cyclic motility was unrelated to glucose levels in the 3rd trimester.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that maternal hyperglycemia does affect fetal movement during the 3rd trimester in normal pregnancies (Aladjem, Feria, Rest, Gull, & O'Connor, 1979;Edelberg, Dierker, Kalhan, & Rosen, 1985;Gelman, Spellacy, Wood, Birk, & Buhi, 1980;Goodman, 1980). However, none of the studies has focused on cyclic motility, the direction of the effects are not consistent between studies, and numerous others have reported no effects (e.g., Bocking, Adamson, Cousin, Campbell, Carrnichael, Natale, & Patrick, 1982;Lewis, Trudinger, & Mangez, 1978;Natale, Richardson, & Patrick, 1983) including two studies of diabetics (Holden, Jovanovic, Dmzin, & Peterson, 1984;Wladimiroff & Roodenburg, 1982). Finally, the evidence from the present study linking parametric changes in cyclic motility with maternal glucose control must be tempered by the fact that the transient absence of cyclic motility was unrelated to glucose levels in the 3rd trimester.…”
Section: Discussionmentioning
confidence: 99%
“…Foetal breathing movements, but not gross foetal body movements, have been shown to be affected by increased maternal glucose levels (Bocking et al, 1982;Lewis et al, 1978), indicating that blood sugar levels may not affect gross movements. Similarly, foetal body movements are unaffected by maternal alcohol consumption, while foetal breathing and eye movements are transiently affected (McLeod et Biomechanics of foetal movement al., 1983;Mulder et al, 1998).…”
Section: External Influences Affecting Foetal Movementsmentioning
confidence: 99%
“…They have been defined as downward movement of the diaphragm with outward movement of ab dominal contents and inward displacement of the thorax [60], It is now well established that breathing is a normal feature of fetal life which is episodic in nature, with circadian and ultradian biological rhythms [30,[61][62][63][64] and a tendency to be stimulated by glucose [65][66][67][68] and carbon dioxide [69,70] and inhibited by hypoxia [61,71,72], Much data have been accumulated on fetal breathing in chronically instrumented fetal animal prepa rations, especially the fetal Iamb. With the development of noninvasive technology for fetal observation, interest in fetal breathing extended to its use as a parameter of well being in the human fetus [73][74][75][76][77].…”
Section: Hiccups and Breathing In The Human Fetusmentioning
confidence: 99%